2021
DOI: 10.1186/s12933-021-01397-1
|View full text |Cite
|
Sign up to set email alerts
|

Visit-to-visit fasting blood glucose variability and lifetime risk of cardiovascular disease: a prospective study

Abstract: Aims Previous studies suggested an adverse association between higher fasting blood glucose (FBG) variability and cardiovascular disease (CVD). Lifetime risk provides an absolute risk assessment during the remainder of an individual’s life. However, the association between FBG variability and the lifetime risk of CVD is uncertain. Objective We aimed to investigate the effect of the visit-to-visit FBG variability on the lifetime risk of CVD. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…Subsequently, higher fasting plasma glycaemic variability, an indicator of chronic glycaemic variability, was confirmed to be linked to the increase in lifetime risk of cardiovascular disease, including participants without cardiovascular disease aged 18–98 years with a median follow-up of 7.0 years. 10 Another recent meta-analysis showed that GV was associated with poor prognosis in coronary heart disease, but this study only used MAGE calculated using CGMS during hospitalization as an indicator of GV. 36 Herein, our results expanded these findings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, higher fasting plasma glycaemic variability, an indicator of chronic glycaemic variability, was confirmed to be linked to the increase in lifetime risk of cardiovascular disease, including participants without cardiovascular disease aged 18–98 years with a median follow-up of 7.0 years. 10 Another recent meta-analysis showed that GV was associated with poor prognosis in coronary heart disease, but this study only used MAGE calculated using CGMS during hospitalization as an indicator of GV. 36 Herein, our results expanded these findings.…”
Section: Discussionmentioning
confidence: 99%
“…6 Recent studies indicated that GV is correlated with a wide variety of diseases resulting in poor prognoses such as sepsis, 7 autonomic dysfunction, 8 and cardiovascular disease 9 in patients with or without diabetes. [10][11][12] The adverse consequences of GV mainly include all-cause, contrast-induced nephropathy, 13 instent restenosis, 14 and so on. In addition, GV has been hypothesized to be deleterious in ACS patients.…”
Section: Introductionmentioning
confidence: 99%
“…High glycemic variability seems to exert more detrimental effects than persistent hyperglycemia on the pathogenesis of diabetic cardiovascular complications [10]. Previously, glycemic variability has been used to predict the diabetic complications, cardiovascular adverse events, and mortality among individuals with or without diabetes [21][22][23][24]. However, whether glycemic variability could serve as an independent risk factor for digestive cancers remained unknown.…”
Section: <001mentioning
confidence: 99%
“…Previous studies have suggested that glucose variability may lead to hypoglycaemia, wide postprandial glucose excursions, and the progression of atherosclerosis, thus affecting the development of diseases later in life 8‐10 . Empirical evidence has shown that greater intra‐individual variation in fasting blood glucose (FBG) is associated with a higher risk of hyperglycaemia, hypoglycaemia and premature mortality 11,12 . Clinical inertia and treatment nonadherence have been major challenges in efforts to optimize glucose‐lowering therapies 13 .…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] Empirical evidence has shown that greater intra-individual variation in fasting blood glucose (FBG) is associated with a higher risk of hyperglycaemia, hypoglycaemia and premature mortality. 11,12 Clinical inertia and treatment nonadherence have been major challenges in efforts to optimize glucose-lowering therapies. 13 The goal of blood glucose control is to reduce glucose levels and glycaemic variability.…”
Section: Introductionmentioning
confidence: 99%